Porta Futuro Lazio: l'innovazione possibile nel servizio pubblico per lo sviluppo dell'occupabilità in ottica lifelong learning - Massimiliano Smeriglio (LED Edizioni Universitarie, 2018)
The country is paying the consequences of a harsh economic and a social crisis that have wholly characterized the last decade. Citizens have been waiting so long for the public service's reform aimed to the employment development and to the matching between job-demand and job-offer. The current common perception shows how the Employment Centers do not seem able to give effective responses to citizen's professional expectations and entreprise's requirements. The article describes the evolution, the methodology and the results of the European best practice Porta Futuro. A particular emphasis is put on the results of the service's innovation. This consist in taking charge, even emotionally, of citizens in very hard employment situations, offering them continuing education according to a pedagogical approach that invests in empowerment and awareness. The text, which includes a depth research on service's functionality and the possibility to replicate it on a national level, is a contribution to facilitate the research of professional opportunities through the typical Italian society cultural heterogeneity.